2022
DOI: 10.3102/00346543221094083
|View full text |Cite
|
Sign up to set email alerts
|

Mind the Gap Between Comprehension and Metacomprehension: Meta-Analysis of Metacomprehension Accuracy and Intervention Effectiveness

Abstract: Research has consistently demonstrated that learners are strikingly poor at metacognitively monitoring their learning and comprehension of texts. The aim of the present meta-analysis is to explore three important questions about metacomprehension: (a) To what extent can people accurately discriminate well-learned texts from less well learned ones? (b) What are the (meta)cognitive causes of poor metacomprehension accuracy? and (c) What interventions improve the accuracy of metacomprehension judgments? In total,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 162 publications
2
14
0
1
Order By: Relevance
“…In contrast, no changes were seen in any of the activity conditions in relative accuracy, that is predicting comprehension across the set of topics. While generative activities have tended to produce benefits in metacomprehension for expository science texts (Fukaya, 2013; Griffin et al, 2008, 2019; Griffin, Mielicki, et al, 2019; Jaeger & Wiley, 2014; Prinz et al, 2020; Wiley, Griffin, et al, 2016; Yang et al, 2023), this study identifies a boundary condition showing that not all generative activities are effective for improving relative accuracy. Further, the results are consistent with work showing that practice tests alone are insufficient to help students develop appropriate expectations that may allow them to more accurately monitor their relative levels of comprehension on new material (Griffin, Wiley, et al, 2019).…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…In contrast, no changes were seen in any of the activity conditions in relative accuracy, that is predicting comprehension across the set of topics. While generative activities have tended to produce benefits in metacomprehension for expository science texts (Fukaya, 2013; Griffin et al, 2008, 2019; Griffin, Mielicki, et al, 2019; Jaeger & Wiley, 2014; Prinz et al, 2020; Wiley, Griffin, et al, 2016; Yang et al, 2023), this study identifies a boundary condition showing that not all generative activities are effective for improving relative accuracy. Further, the results are consistent with work showing that practice tests alone are insufficient to help students develop appropriate expectations that may allow them to more accurately monitor their relative levels of comprehension on new material (Griffin, Wiley, et al, 2019).…”
Section: Discussionmentioning
confidence: 80%
“…During self-regulated study, students decide on their own when to read, what to read, and how much to read. Because the self-regulated study process also includes decisions of whether and what to re-read, the ability to accurately monitor one’s comprehension from text, or to engage in accurate metacomprehension, can also play an important role in determining the level of understanding that students may actually achieve when learning from text (Thiede et al, 2003; Wiley, Thiede, et al, 2016; Yang et al, 2023).…”
Section: Benefits Of Examples For Learning Declarative Concepts From ...mentioning
confidence: 99%
“…Sin duda, reflexionar cuando se aprende es un reto y no pocos estudiantes tienen dificultades para el seguimiento metacognitivo de su aprendizaje, por lo que se requieren estrategias pedagógicas que garanticen su desarrollo (Yang et al, 2022).…”
Section: )unclassified
“…Relative monitoring accuracy is expressed as a correlational measure (typically gamma correlation) between JOLs and comprehension test performance across texts (indicating if students can accurately judge which texts were better understood than others; Griffin et al, 2019). Absolute monitoring accuracy, which is also what the present study focusses on, is computed per text, as a difference score between students' JOL on a text and their actual comprehension of that text as measured by a comprehension test; if the difference between JOL and actual comprehension is zero, monitoring is fully accurate (Griffin et al, 2019; Schraw, 2009; Yang et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…The timing of the diagramming activity might be important for this benefit to arise, though: Van Loon et al (2014) found that immediate diagramming (i.e., completing the diagram immediately after reading a text) improved comprehension test performance compared to delayed diagramming (first reading several texts and then completing diagrams on those texts) or no diagramming. Nevertheless, even though generative tasks like diagramming have been found to lead to more accurate monitoring judgements, there is still substantial room for improvement in monitoring accuracy (Prinz et al, 2020b;Yang et al, 2023). Thus, there is a need to optimize this intervention by drawing students' attention towards the diagnostic cues that can be inferred from the diagrams.…”
mentioning
confidence: 99%